Pengaruh Pengawasan & Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Mitra Terminal Kaltim di Kutai Kartanegara - Asmi Suandari (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
Abstract. This study aims to determine the effect of supervision on employee performance and work discipline on employee performance, and to determine the effect of supervision and work discipline on employee performance both partially and simultaneously at PT Mitra Terminal Kaltim in Kutai Kartanegara, East Kalimantan. quantitative. Data collection techniques using validated and reliability questionnaires and interviews. Data analysis techniques using the classical assumption test, multiple linear regression, T test, F test, and the coefficient of determination. Data processing in this study used the SPSS (Statistics Package for the Social Science) software program. The total population in this study was 40 employees. The results of this study prove that partially supervision has no effect on employee performance. While Work Discipline has a significant and significant effect on Employee Performance. Simultaneously it shows that Supervision and Work Discipline have a significant effect on Employee Performance at PT Mitra Terminal Kaltim Kutai Kartanegara.